Studi Perbandingan Kekuatan Profil IWF, Hexagonal Beam dan Octagonal Beam dengan Perhitungan Manual dan Metode Elemen Hingga: Comparative Study of IWF Profile Strength, Hexagonal Beam and Octagonal Beam with Manual Calculations and Finite Element Method - Zarmihan, Rezaldi Pramanda; Pratiwi, Vitta; Krisnadi, Sutedjo (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2022)
A castellated beam is formed from the IWF body profile cutting pattern, and the cuts are then adjusted between the pieces and then welded to put them back together. The advantage of modifying the IWF profile into a castellated beam is that it can increase the moment of inertia of the section (Ix), and this increase affects the bending capacity of the castellated beam profile and the ability of the profile to withstand loads. However, these profile modifications have limitations that are used to minimize the occurrence of extreme failures, and one of the limitations is that the modified profile may not exceed 50% of the height increase from the initial profile height. In this study, the profile capabilities of IWF, Hexagonal Beam, and Octagonal Beam will be compared with a total of 3 models of centralized loads that can be carried. In this study, two methods will be used, namely manual calculation and finite element method. From the results of the analysis that has been carried out with both methods, it can be seen that the effect of modifying the IWF profile into hexagonal beams and octagonal beams can increase the load capacity of the profiles. However, the highest profile capability increase occurred in model 1 or IWF profile 150x75x5x7, which was modified to model 2 or hexagonal beam 220x75x5x7. The increase in the profile was 34.83% for manual method calculations and finite element method calculations, an increase of 12.15 %. The highest comparison between the manual calculation method and the finite element method occurs in the hexagonal profile beam measuring 240x75x5x7 with a difference of 21.39%. Based on the research that has been done, it can be concluded from the three profiles that it is better if the profile used is model 2.